2021
DOI: 10.3390/molecules26154405
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of Phenolic Compounds from Kiwifruit and Persimmon

Abstract: Fruit used in the common human diet in general, and kiwifruit and persimmon particularly, displays health properties in the prevention of heart disease. This study describes a combination of bioactivity, multivariate data analyses and fluorescence measurements for the differentiating of kiwifruit and persimmon, their quenching and antioxidant properties. The metabolic differences are shown, as well in the results of bioactivities and antioxidant capacities determined by ABTS, FRAP, CUPRAC and DPPH assays. To c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
2
5
1
Order By: Relevance
“…Finally, in the persimmon extracts, the most abundant compound was kaempferol-3-O-glucoside, and kaempferol derivates were also detected. Other studies have shown that kaempferol and derivates and quercetin are common compounds in persimmon [48][49][50][51]. Nevertheless, in contrast, Yaqub et al reported that caffeic acid, p-coumaric acid, and ferulic acid were present in large quantities in persimmon extracts, which were not detected in our study [48].…”
Section: Phenolic Compoundscontrasting
confidence: 91%
“…Finally, in the persimmon extracts, the most abundant compound was kaempferol-3-O-glucoside, and kaempferol derivates were also detected. Other studies have shown that kaempferol and derivates and quercetin are common compounds in persimmon [48][49][50][51]. Nevertheless, in contrast, Yaqub et al reported that caffeic acid, p-coumaric acid, and ferulic acid were present in large quantities in persimmon extracts, which were not detected in our study [48].…”
Section: Phenolic Compoundscontrasting
confidence: 91%
“…The 3D-FL was measured at emission wavelengths between 200 and 795 nm, and the initial excitation wavelength was 200 nm. For comparison of the obtained results, caffeic acid, quercetin, and tannic acid were used [9,10]. The binding properties of wine to human serum albumin (HSAlb) and fibrinogen were evaluated by using 2D-and 3D-FL.…”
Section: Fluorometric Studiesmentioning
confidence: 99%
“…The analysis of the results indicates a promising role for food polyphenols in preventing thrombosis and cardiovascular diseases, but, at the same time, suggests caution when transferring the in vitro findings in vivo [4][5][6]. It was reported in a number of recent studies [7][8][9][10] that the consumption of beer, wine, and fruits has already been associated with a multitude of beneficial effects due to their high polyphenolic content. Beverages have to be consumed moderately in order to obtain their positive influence on health.…”
Section: Introductionmentioning
confidence: 99%
“…Since the fluorescence quenching can be a common phenomenon with natural extracts, 40,41 we employed a quenching control (Quench, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, this effect could be even higher due to the autofluorescence observed with the extracts. 39 Since the fluorescence quenching can be a common phenomenon with natural extracts, 40,41 we employed a quenching control (Quench, Fig. 1).…”
Section: Inhibitory Effects Of Sfe Against Mpromentioning
confidence: 99%